2016
DOI: 10.1111/phpp.12274
|View full text |Cite
|
Sign up to set email alerts
|

UVR protection influences fructosamine level after sun exposure of healthy adults

Abstract: Appropriate sunscreen use during sunbathing resulted in decreased fructosamine concentrations, while inadequate UVR protection resulted in its increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…38 Conversely, increased HDL-cholesterol levels were observed in individuals given advice to increase sun exposure in two studies. 37,38 While no significant effects of sun exposure on blood glucose were observed, 37,38,40 reduced HbA1c levels were observed in one study, 37 and blood glucose levels may have been 'normalised' in individuals with prediabetes in the sun exposure advice study arm of another study. 39…”
Section: Sun Exposurementioning
confidence: 90%
See 4 more Smart Citations
“…38 Conversely, increased HDL-cholesterol levels were observed in individuals given advice to increase sun exposure in two studies. 37,38 While no significant effects of sun exposure on blood glucose were observed, 37,38,40 reduced HbA1c levels were observed in one study, 37 and blood glucose levels may have been 'normalised' in individuals with prediabetes in the sun exposure advice study arm of another study. 39…”
Section: Sun Exposurementioning
confidence: 90%
“…Most identified studies had small sample sizes (≤100 participants), were short in duration (≤12 weeks for 13/20 studies in which study length was reported), involved older adults (>35 years-of-age), and compared pre-and post-intervention levels of a limited number of measures. Overall, few studies assessed markers of glucose metabolism; beneficial effects of sun exposure advice were seen in some, 37,39 but not all, 38,40 studies. Measures of adiposity, including BMI and waist/hip circumference, were not significantly modified by UVR phototherapy/sun exposure advice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations